Breastfeeding in Turkey: practices, barriers, and cultural dynamics for global insights - Celebier, Kaan; Yigit, Metin; Kalayci, Furkan; Kirgil, Berrak Naz; Yilmaz, Naci; Dogan, Ali Evrim; Tolunay, Orkun (Frontiers in Pediatrics, 2025)
ObjectiveBreastfeeding is globally recognized as the cornerstone of infant nutrition, offering unparalleled benefits for maternal and child health. However, exclusive breastfeeding rates remain below international targets, influenced by sociocultural, economic, and individual factors. This study aims to investigate breastfeeding practices in Türkiye, identify influencing factors, and compare these findings with global trends to highlight both commonalities and country-specific dynamics.MethodsThis cross-sectional study was conducted at Ankara Bilkent City Hospital between June and August 2024, with 392 mothers of children aged 2–5 years. Data were collected through structured surveys addressing demographics, breastfeeding practices, and formula use. Statistical analyses were performed using SPSS, with p < 0.05 considered significant.ResultsExclusive breastfeeding during the first six months was reported by 37.5% and was influenced by perceived milk insufficiency, socioeconomic factors, and extended family involvement. Cesarean delivery was associated with increased formula use, and lower-income families were less likely to sustain breastfeeding to 24 months. Contrary to global patterns where family support is beneficial, extended family involvement in Türkiye negatively affected exclusive breastfeeding. In multivariable models, maternal chronic illness and cesarean delivery increased the odds of formula use (OR = 1.6; 95% CI = 0.98–2.79; p = 0.04 and OR = 1.8; 95% CI = 1.21–2.81; p = 0.004). Not receiving support from extended family and normal spontaneous vaginal delivery increased the odds of exclusive breastfeeding in the first six months (OR = 1.9; 95% CI = 1.25–2.91; p = 0.003 and OR = 1.5; 95% CI = 1.02–2.47; p = 0.041). University-level education was associated with initiating complementary feeding after six months (OR = 2.1; 95% CI = 0.27–0.80; p = 0.006). No significant model was established for total breastfeeding duration.ConclusionsBreastfeeding practices in Turkey reflect global challenges, including maternal perceptions of insufficient milk supply and economic barriers, while also highlighting unique cultural dynamics, particularly the influence of extended family. Addressing these issues requires a dual approach: implementing universal interventions, including healthcare professional guidance and breastfeeding education, and developing culturally specific strategies to mitigate the negative impact of traditional norms on exclusive breastfeeding rates. Policymakers should prioritize reducing cesarean delivery rates and strengthening support systems for low-income mothers. Comprehensive, multifaceted interventions are essential to improve breastfeeding outcomes and align national practices with international health goals.